Penerapan Sistem Pengendalian Berbasis IoT (Internet Of Things) Untuk Meningkatkan Efisiensi Proses Pengeringan Pupuk Granul Berbahan Eco Enzim - Danang, Danang; Sasmoko, Dani; Swastuti, Endang (Universitas Gajah Putih, Indonesia, 2023)
In Indonesia, we see a lot of waste in society that can actually still be reused. By using Eco Enzym, the waste can be processed into many derivative products. Residents of RW VII Gombel Permai, Ngesrep Village, Banyumanik District, Semarang have processed this product, but have experienced problems in the drying process, which is still done manually in the sun. The Community Care Team took the initiative to apply IoT technology to this technology-based dryer. The convenience is that using this tool does not require sunlight, uses UV light so it can kill bad bacteria and can be monitored remotely. Residents are enthusiastic about using it because the process is faster, doesn't require too much physical effort and is cheaper to make.